Clinical and microbiological observations on CDC group DF-3, a gram-negative coccobacillus. - Gill, V J (1991)
Sequential stool cultures submitted for routine culture were screened for the presence of CDC group DF-3. Of 690 specimens, 11 (1.6%) yielded moderate to heavy growth of DF-3. Information on the 11 patients from whom these specimens were obtained showed that 4 had a history of prolonged diarrheal disease that resolved after specific therapy to eradicate DF-3, while for the other 7 patients no clear role could be established. Microbiological characterization of the stool isolates and 10 CDC strains of DF-3 suggested the presence of two subtypes within the group. Antibiotic susceptibility studies showed DF-3 to be relatively resistant to a wide variety of antibiotics.